Hands-on ethical hacking and network defense - Simpson, Michael T. 1954-; Antill, Nicholas D.; Wilson, Robert S. (Cengage Learning, 2021)
Hands-on ethical hacking and network defense, 4th edition, equips you with the knowledge and skills to protect networks using the tools and techniques of an ethical hacker. The authors explore the concept of ethical hacking and its practitioners -- explaining their importance in protecting corporate and government data -- and then deliver an in-depth guide to performing security testing. Thoroughly updated, the text covers new security resources, emerging vulnerabilities and innovative methods to protect networks, mobile security considerations, computer crime laws and penalties for illegal computer hacking. A final project brings concepts together in a penetration testing exercise and report, while virtual machine labs, auto-graded quizzes and interactive activities in the online learning platform help further prepare you for your role as a network security professional.